2016
DOI: 10.13189/ujpa.2016.100306
|View full text |Cite
|
Sign up to set email alerts
|

On the Nuclear Coupling of Proton and Electron

Abstract: We study both experimentally and theoretically the creation of a new physical entity, a particle in which the proton and electron form a stable pair with a tiny size typical for a nucleon. A new theoretical approach to study atomic, sub atomic and nuclear systems is suggested. In the framework of this new approach, which takes into account a submicroscopic concept of physics, we discuss similar experimental results of other researchers dealing with low energy nuclear reactions in a solid, plasma, sonofusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, in light of the topic presented in this paper, it cannot also be ruled out that during the formation of a subhydrogen [50], an electron, absorbing the inerton cloud of the tungsten atom, passed into a muon. Thus, the produced subhydrogen atoms could be really massive excited proton-muon pairs.…”
Section: Neutrino Massmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in light of the topic presented in this paper, it cannot also be ruled out that during the formation of a subhydrogen [50], an electron, absorbing the inerton cloud of the tungsten atom, passed into a muon. Thus, the produced subhydrogen atoms could be really massive excited proton-muon pairs.…”
Section: Neutrino Massmentioning
confidence: 84%
“…In interesting research, we [50] observed how hydrogen atoms transformed into hydrogen atoms with a mass up to around 200 times greater than their standard mass. At a plasma discharge in a hydrogen atmosphere, a proton moving to the cathode under conditions of pulse resonance knocked out an inerton cloud from a tungsten atom.…”
Section: Neutrino Massmentioning
confidence: 99%
“…In fact, at our experimental and theoretical study, 24 we found that at some peculiar conditions a proton could couple with an electron absorbing an inerton cloud of the nearest heavy atom, which resulted in the creation of a quite stable subhydrogen whose size could only be about 1 fm. Similarly, a subhelium atom was generated and it was predicted the possibility of heavier subatoms with the nuclear size of around 1 nm.…”
Section: Final Remarksmentioning
confidence: 87%